2017
DOI: 10.4103/ortho.ijortho_266_16
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Laminectomy with Lateral Mass Screw Fixation in Cervical Spondylotic Myelopathy

Abstract: Background:Anterior cervical decompression and fusion is the standard procedure used for treating patients with cervical myelopathy. However, these procedures are associated with complications such as pseudarthrosis, construct failure, and neurological complications. Posterior cervical laminectomy and instrumentation is an alternative procedure to treat multilevel cervical myelopathy. In this study, we raised questions whether instrumentation is required at all levels and whether stabilizing the spine in neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…In recent years, fusion procedures have increased primarily among reports from overseas. Posterior decompression combined with fusion using posterior instrumentation along with laminoplasty and laminectomy might be more beneficial than using laminoplasty alone in restoring normal cervical lordosis 130) , stabilizing intervertebral mobility, and preventing postoperative kyphosis deformity 131) . However, compared with laminoplasty, it has been reported that the incidence of postoperative neurological complications is higher in laminectomy combined with fusion 132) .…”
Section: Commentarymentioning
confidence: 99%
“…In recent years, fusion procedures have increased primarily among reports from overseas. Posterior decompression combined with fusion using posterior instrumentation along with laminoplasty and laminectomy might be more beneficial than using laminoplasty alone in restoring normal cervical lordosis 130) , stabilizing intervertebral mobility, and preventing postoperative kyphosis deformity 131) . However, compared with laminoplasty, it has been reported that the incidence of postoperative neurological complications is higher in laminectomy combined with fusion 132) .…”
Section: Commentarymentioning
confidence: 99%
“…Основными факторами, влияющими на клинический исход после ламинэктомии и винтовой фиксации за боковые массы, являются: эффективная декомпрессия спинного мозга и его корешков, плотная фиксация винта в боковой массе и отсутствие его миграции в полость межпозвонкового диска и/или позвоночный канал [22].…”
Section: таблица 2 характеристика осложнений у исследуемой группы пацunclassified
“…По данным Singrakhia et al [22], среднее улучшение по шкале mJOA составило с 8,56 до 13,57, по шкале Nurick с 2,59 до 0,66, изменения по шкале Cooper с 1,75 до 0,31 для верхних конечностей и с 2,14 до 0,56 для нижних конечностей.…”
Section: таблица 2 характеристика осложнений у исследуемой группы пацunclassified
“…В настоящее время отсутствует приоритетность в определении оптимального способа задней декомпрессии и стабилизации, a используемые хирургические методики имеют специфические преимущества и недостатки [12,13]. Так, ЛФ позволяется уменьшить послеоперационную нестабильность и дооперационный кифоз [14,15]. В свою очередь ЛП обеспечивает сохранение естественной биомеханики шейного отдела, целостность задних анатомических структур и физиологического лордоза [16,17].…”
Section: Introductionunclassified